Effects of Irrigation and Cluster Thinning on Tempranillo Grape and Wine Composition - Gamero, E.; Moreno, D.; Talaverano, I.; Prieto, M.H.; Guerra, M.T.; Valdés, M.E. (South African Journal of Enology and Viticulture, 2016)
With the aim of understanding the effects of water stress and cluster load on berry composition and wine quality, a four-year field test was conducted in a cv. Tempranillo vineyard in Extremadura (Spain). When the first berries appeared to be changing colour (onset of véraison), grapevines were subjected to two different irrigation regimes, one supplying 100% of crop evapotranspiration, and the other 25%. In addition, two cluster load levels were tested for each irrigation regime: seven to nine and four to five clusters/m2 planting area. Both irrigation and thinning had an impact on most of the parameters analysed in the grapes and the wines, although the thinning effect was in general higher than the irrigation effect. Thus, deficit irrigation reduced malic acid and the titratable acidity of Tempranillo grape juice, while cluster thinning increased all parameters analysed, except potassium concentrations. Similarly, the wine composition was also affected differently by irrigation and by cluster thinning. Deficit irrigation reduced pH and increased titratable acidity, total phenol index and colour parameters, while cluster thinning increased alcohol content, anthocyanin and colour intensity, and reduced pH and colour. The effect of the cluster thinning technique was independent of the irrigation regime in most of the wine parameters analysed, except for total phenol index, where the effect of deficit irrigation (DI) was more pronounced in grapevines also subjected to the cluster thinning treatment.